9q31.1q31.3 deletion in two patients with similar clinical features: A newly recognized microdeletion syndrome?. Issue 3 (20th December 2013) - Mucciolo, M.; Magini, P.; Marozza, A.; Mongelli, P.; Mencarelli, M.A.; Hayek, G.; Tavalazzi, F.; Mari, F.; Seri, M.; Renieri, A.; Graziano, C.
ABSTRACT Interstitial deletions of the long arm of chromosome 9 are rare and most patients have been detected by conventional cytogenetic techniques. Disparities in size and localization are large and no consistent region of overlap has been delineated. We report two similar de novo deletions of 6.3 Mb involving the 9q31.1q31.3 region, identified in two monozygotic twins and one unrelated patient through array‐CGH analysis. By cloning the deletion breakpoints, we could show that these deletions are not mediated by segmental duplications. The patients displayed a distinct clinical phenotype characterized by mild intellectual disability, short stature with high body mass index, thick hair, arched eyebrows, flat profile with broad chin and mild prognathism, broad, and slightly overhanging tip of the nose, short neck with cervical gibbus. The twin patients developed a metabolic syndrome (type 2 diabetes, hypercholesterolemia, vascular hypertension) during the third decade of life. Although long‐term follow‐up and collection of additional patients will be needed to obtain a better definition of the phenotype, our findings characterize a previously undescribed syndromic disorder associated with haploinsufficiency of the chromosome 9q31.1q31.3 region. © 2013 Wiley Periodicals, Inc.